EFFECT OF SPICES AND SWEET VIOLET EXTRACTS TO REPLACE ANTIBIOTICS AND ANTIOXIDANTS IN FEED ON BROILER PERFORMANCE, HEMATOLOGY, LIPID PROFILE AND IMMUNITY - S. Waheed; A. Hasnain; A. Ahmad; O. M. Tarar; Z. Yaqeen; T. M. Ali (Journal of Animal and Plant Sciences, 2017)
A research trial was conducted on 120 broilers, dividing them in eight feeding groups of 3 replicates of 5 birds. Ration F1 was Positive control (PC) diet with antibiotic and synthetic antioxidants. Ration F2 was negative control (NC). Other diets were having extracts as following: F3 was NC+ fenugreek, F4 was NC +black cumin seed, F5 was NC + sweet violet, F6 was NC + ajwain, F7 was PC + ajwain, fenugreek and sweet violet and F8 was NC diet+ ajwain, fenugreek and sweet violet. All the treatments with extracts had significant difference (p≤0.05) in weight gain and feed conversion ratio (FCR) as compared to NC diet. Dressing percentage and breast meat improved in F6, F7 and F8 treatments. Pancreas, liver and thymus size significantly reduced (p≤0.05) in diet F7 and F8. Bursa weights were significantly higher in F3, F4 and F6 (p≤0.05) compared with F2. Hemoglobin, platelets and WBC increased significantly in F3, F4, F5 and F8 group (p≤0.05), Cholesterol reduced in F5, F6 and F8 and triglyceride in F3, F5, F6, F7 and F8 group as compared to F2. There was non-significant difference (P>0.05) in RBC, lymphocyte, MCH and MCV counts. Treatments with natural extracts significantly (p≤0.05) increased ND titre.
Keywords: broiler; plant extracts; antioxidants; polyphenols; organ size